The difference of primary school teachers’ online teaching satisfaction in subject and educational level - Zhu, Yonghai; Liu, Di; Xu, Yingying (Frontiers in Psychology, 2023)
The growth of online education requires high-quality online teaching. Teachers’ satisfaction with online teaching is of great significance for improving online teaching effectiveness. This study was to explore the primary school teachers’ online teaching satisfaction during the spread of COVID-19, who have experienced online teaching, and explore whether there were differences of teachers’ online teaching satisfaction in subject and educational level. 939 teachers from Shanghai participated in the study. The non-parametric Mann-Whitney U test and Kruskal-Wallis test of variance were performed. Results showed that teachers’ online teaching satisfaction was at a high level. Moreover, there was a significant difference in teachers’ subject and educational level on online teaching satisfaction. Teachers of different subjects have significant differences in resource suitability (RS). Therefore, it is recommended that each discipline should develop the online teaching resources to support teachers’ online teaching. Teachers should also improve their digital and technological literacy to help promote the online teaching effectiveness. The findings provide reference and contribution for measuring teacher's online teaching satisfaction.